The missiological implications of epistemological shifts : affirming truth in a modern/postmodern world - Hiebert, Paul G., 1932-2007 (Christian mission and modern culture., 1999)
This book explores the question of epistemology, or theory of knowledge, and its impact upon how we view and do missions in today's world. What must a new convert know or believe? How do they know? How can we translate and communicate Christian teachings interculturally without distorting the message? How should we do missions in an anti-colonial, postmodern era characterized by religious relativism and accusations of Christian imperialism?In struggling with these questions, Paul Hiebert focuses on the epistemological foundations that underlay them. He examines three specific theories of knowle.